2014
DOI: 10.1007/s00424-014-1661-5
|View full text |Cite
|
Sign up to set email alerts
|

Urinary serine proteases and activation of ENaC in kidney—implications for physiological renal salt handling and hypertensive disorders with albuminuria

Abstract: Serine proteases, both soluble and cell-attached, can activate the epithelial sodium channel (ENaC) proteolytically through release of a putative 43-mer inhibitory tract from the ectodomain of the γ-subunit. ENaC controls renal Na(+) excretion and loss-of-function mutations lead to low blood pressure, while gain-of-function mutations lead to impaired Na(+) excretion, hypertension, and hypokalemia. We review an emerging pathophysiological concept that aberrant glomerular filtration of plasma proteases, e.g., pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 133 publications
2
50
0
Order By: Relevance
“…However, after glomerular injury, larger amounts of plasminogen can be filtered and activated in the tubulus lumen. Urokinasetype plasminogen activator lining the tubular epithelium is thought to be the principal enzyme responsible for the generation of active urinary plasmin (2). However, serine protease inhibitors, such as antiplasmin (27) or uristatin (28), have been found to enter the tubular lumen during proteinuria, adding to the complexity of the situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after glomerular injury, larger amounts of plasminogen can be filtered and activated in the tubulus lumen. Urokinasetype plasminogen activator lining the tubular epithelium is thought to be the principal enzyme responsible for the generation of active urinary plasmin (2). However, serine protease inhibitors, such as antiplasmin (27) or uristatin (28), have been found to enter the tubular lumen during proteinuria, adding to the complexity of the situation.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of edema formation is still a matter of debate, and both underfill and overfill mechanisms have been put forward (1). Recent evidence points to the crucial role of proteinuria in promoting sodium retention through activation of the epithelial sodium channel (ENaC) (2), which is known to be an important player in sodium homeostasis and BP control (3). Studies with protein-rich urine from both nephrotic rats and patients have shown a stimulation of ENaC currents in vitro that was attributed to occurrence of the serine protease plasmin in the urine (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Among the three subunits of ENaC, α and γ subunits are activated by cleavage of the inhibitory domain in the extracellular loop, which is mediated by cell-surface or soluble extracellular serine proteases such as prostasin, plasmin and kallikrein (Vallet et al 1997, Narikiyo et al 2002, Svenningsen et al 2015. For example, prostasin promotes the cleavage of the ENaCγ protein inhibitory domain (Narikiyo et al 2002).…”
Section: Mr Signaling In Principal Cells Of the Collecting Ductmentioning
confidence: 99%
“…Each subunit has two membrane-spanning domains and an extracellular loop [27,[30][31][32]. The extracellular domains of α and γ subunits of ENaC are targets for proteases [27,32].…”
Section: Introductionmentioning
confidence: 99%